Quantification and optimization of platinum–molybdenum carbide interfacial sites to enhance low-temperature water-gas shift reaction - Ruiying Li; Jingyuan Shang; Fei Wang; Qing Lu; Hao Yan; Yongxiao Tuo; Yibin Liu; Xiang Feng; Xiaobo Chen; De Chen; Chaohe Yang (Nature Communications)
Abstract Pt/α-MoC1-x catalysts exhibit exceptional activity in low-temperature water-gas shift reactions. However, quantitatively identifying and fine-tuning the active sites has remained a significant challenge. In this study, we reveal that fully exposed monolayer Pt nanoclusters on molybdenum carbides demonstrate mass activity that exceeds that of bulk molybdenum carbide catalysts by one to two orders of magnitude at 100–200 °C for low-temperature water-gas shift reactions. This advancement is driven by the precise quantification and elucidation of active sites along the Pt-molybdenum carbide interfacial perimeter. By combining sacrificial CO adsorption per Pt atom, Density Functional Theory calculations, and CO chemisorption measurements, we establish a direct correlation between the monolayer Pt nanocluster size and the number of interfacial perimeters on Pt/α-MoC1-x catalysts. In this work, these findings provide key insights into the active site configuration of Pt/α-MoC1-x catalysts and open pathways for innovative catalyst design, with the interfacial perimeter identified as a crucial factor in enhancing catalytic performance.